2017
DOI: 10.1002/14651858.cd006750.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitor withdrawal or tapering for kidney transplant recipients

Abstract: CNI avoidance increased acute rejection and CNI withdrawal increases acute rejection but reduced graft loss at least over the short-term. Low dose CNI with induction regimens reduced acute rejection and graft loss with no major adverse events, also in the short-term. The use of mTOR-I reduced CMV infections but increased the risk of acute rejection. These conclusions must be tempered by the lack of long-term data in most of the studies, particularly with regards to chronic antibody-mediated rejection, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 337 publications
2
36
0
1
Order By: Relevance
“…Recent meta‐analysis and literature reviews provided the evidence that early withdrawal of CNI and introduction of mTORi might induce the de novo glomerulonephritis and graft loss . However, the Cochrane database reported that mTORi might increase the acute rejection, but the effect on long‐term graft loss was still uncertain . From our result, the percentage of reentry of dialysis in the mTORi users is similar to the patients with mTORi nonusers.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Recent meta‐analysis and literature reviews provided the evidence that early withdrawal of CNI and introduction of mTORi might induce the de novo glomerulonephritis and graft loss . However, the Cochrane database reported that mTORi might increase the acute rejection, but the effect on long‐term graft loss was still uncertain . From our result, the percentage of reentry of dialysis in the mTORi users is similar to the patients with mTORi nonusers.…”
Section: Discussionsupporting
confidence: 61%
“…It is interesting that the percentage of comorbidities such as hypertension, diabetes mellitus, ischemic heart disease, and cerebrovascular disease was higher in the mTORi users. In contrast to CNI, the nephrotoxicity and hypertension were less common in the mTORi users, and pretransplantation comorbidities might influence the clinicians’ decision in choosing the immunosuppressive agents. Hyperglycemia and hyperlipidemia were linked to the mTOR inhibitors, but Lamming et al reported that mTORi provided longevity beyond the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations